THE DYNAMICS OF COURT DECISIONS IN THE CIVIL DISPUTE OVER GOLD SALES BETWEEN PT ANTAM TBK AND BUDI SAID AND ITS IMPLICATIONS FOR THE APPLICATION OF CIVIL LAW IN INDONESIA - Martha Hasanah Rustam; Duwi Handoko; Afrinaldy Rustam; Muhammad April (Fakultas Pertanian, 2025)
This study examines the litigation trajectory of the gold sales dispute between PT Aneka Tambang Tbk (Antam) and Budi Said across four judicial levels in Indonesia: the Surabaya District Court, the Surabaya High Court, the Supreme Court at the cassation stage, and two rounds of judicial review (Peninjauan Kembali). Employing a normative legal research design, the analysis draws on statutory provisions, court decisions, and scholarly literature to assess the application of tort elements in sale contracts. Findings reveal divergent interpretations of tort elements (unlawful act, loss, causation, and fault) at each judicial tier: the District Court and the Supreme Court (cassation and first judicial review) affirmed the presence of tort, obligating Antam to deliver 1.136 tons of gold or pay compensation; the High Court rejected the claim entirely; and the second judicial review reversed Antam’s obligation based on new criminal findings against Budi Said. These oscillating verdicts generate legal uncertainty, blur the line between breach of contract and tort, and underscore the need for harmonization between civil and criminal proceedings and the standardization of tort evidentiary rules. Recommended measures include issuing consistent Supreme Court jurisprudential guidelines, clarifying corporate authority in contractual engagements, and strengthening internal corporate oversight.